2001
DOI: 10.1039/b104761m
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the valence and core photoemission spectra of C60

Abstract: The photoionization cross section and angular distribution relative to all primary ionizations in have been C 60 computed employing a convergent one-centre expansion and an LDA hamiltonian over an extended energy range. The results show the presence of very sharp shape resonances both in the valence and core spectra. Good agreement is obtained with available experimental data, notably the HOMO/HOMO-1 oscillations, the absolute total photoabsorption and the available photoionization spectra, suggesting that mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 32 publications
1
51
1
Order By: Relevance
“…8) They concluded that the relative partial cross section for double photoionization of C 60 should be about one third as large as Kou et al had expected. In this connection, Reinköster et al 6) and Juranic et al 7) have reported that the sum of the relative partial cross sections for C 60 zþ (z ¼ 1{ 3) from C 60 is consistent with the photoabsorption cross section of Colavita et al 9) To obtain an absolute photoionization or photoabsorption cross section curve of C 60 is another important issue that still remains to be settled. Generally speaking, if the sample is nonvolatile and its vapor pressure data is unreliable, one should be confronted with many difficulties in accurately estimating the absolute number density and effective path length of the interaction region in a windowless sample gas chamber.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…8) They concluded that the relative partial cross section for double photoionization of C 60 should be about one third as large as Kou et al had expected. In this connection, Reinköster et al 6) and Juranic et al 7) have reported that the sum of the relative partial cross sections for C 60 zþ (z ¼ 1{ 3) from C 60 is consistent with the photoabsorption cross section of Colavita et al 9) To obtain an absolute photoionization or photoabsorption cross section curve of C 60 is another important issue that still remains to be settled. Generally speaking, if the sample is nonvolatile and its vapor pressure data is unreliable, one should be confronted with many difficulties in accurately estimating the absolute number density and effective path length of the interaction region in a windowless sample gas chamber.…”
Section: Introductionmentioning
confidence: 81%
“…This total cross section curve may accord with the photoabsorption cross section of C 60 , since the photoionization quantum yield is considered to be nearly equal to unity in this h region 5,10) and the contribution of triply or highly charged C 60 zþ is much smaller. Nevertheless, the total cross section proposed by Kou et al 5) was not proportional to the theoretical absolute photoabsorption cross section of C 60 obtained by Colavita et al 9) Very recently, Mitsuke et al investigated the dependence of the detection efficiency of the ion detector on the mass-to-charge ratio (m=z). 8) They concluded that the relative partial cross section for double photoionization of C 60 should be about one third as large as Kou et al had expected.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While weak EX-AFS oscillations in absorption cross sections due to diffraction are nowadays a standard tool for local structure determination in solid state, surface science and biological studies, comparable studies in photoelectron emission in the gas phase are just in their infancy. In fact up to now only two cases have been thoroughly explored: the diatomic homonuclear case, especially N 2 4,11,61,64,69,74,75,77 , after the Cohen-Fano prediction 82 , and the HOMO/HOMO-1 oscillations in C 60 and related systems [86][87][88][89][90][91][92][93][94] . It is becoming clear, however, that such interference/diffraction patterns are an ubiquitous phenomenon, although more complex in nonsymmetrical molecules and further complicated in the valence shell by mixing of different atomic orbitals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…18 A number of models have been put forward to explain the phenomenon, including quantization in a spherical box, 19 diffraction from its edges, 20 and various spherical models. 21 Our interpretation, 22,23 following also ref 18, is that their origin is in interference of electron waves emitted from equivalent centers and is just another manifestation of the interference effects predicted and observed in diatomics. Analogous structures have been uncovered also in the deeper channels 24,25 and in the nondipole parameters.…”
Section: ■ Introductionmentioning
confidence: 94%